On the value of a premium college football player: evaluating the literature - Losak, J. M.; Posmanick, B. J.; Sauer, R. D. (Journal of Sports Economics, 2024)
Over the past decade, the issue of player compensation in college sports has been the subject of several successful legal challenges. Athletes contend that the compensation they receive falls significantly short of the value they generate, attributing this gap to unlawful National Collegiate Athletic Association restrictions. Numerous tools exist in the sports economic literature that estimate the value of college athletes, with an emphasized focus toward premium college football players. In addition to providing updated estimate of player marginal revenue product (MRP), we review past and contemporary methodologies for estimating college player MRPs. We contend that, while presenting some evidence that restrictions on player compensation resulted in the extraction of the majority of the value generated by top college athletes, existing methods leave considerable uncertainty over the magnitude of exploitation.